2022
DOI: 10.3390/ma15217528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiber and Surface Treatment on Airport Pavement Concrete against Freeze–Thawing and Salt Freezing

Abstract: Airport pavement concrete often suffers from freeze–thawing damage in high latitude and cold areas. In addition, the use of aircraft deicer makes the airport pavement concrete suffer from salt-freezing damage. To improve the durability of airport pavement concrete, modified polyester synthetic fiber (FC), cellulose fiber (CF), and basalt fiber (BF) reinforced concrete were prepared in this paper. The mechanical strength, pore structure, and frost resistance (freeze–thawing and salt freezing) of fiber-reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The random distribution of fiber is conducive to strengthening the connectivity of the concrete matrix, thus inhibiting the peeling phenomenon of the concrete surface. Xu, L. [ 27 ] and Li, W.J. [ 28 ] also found that fiber can reduce the mass loss of concrete under freeze-thaw damage, and the existence of fiber makes the overall connection of the structure higher.…”
Section: Resultsmentioning
confidence: 99%
“…The random distribution of fiber is conducive to strengthening the connectivity of the concrete matrix, thus inhibiting the peeling phenomenon of the concrete surface. Xu, L. [ 27 ] and Li, W.J. [ 28 ] also found that fiber can reduce the mass loss of concrete under freeze-thaw damage, and the existence of fiber makes the overall connection of the structure higher.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD technology can perform phase analysis of samples, and the changes in the relative content of a certain component before and after leaching can be analyzed through X-ray diffraction patterns [69]. For example, XRD can be used to compare the differences in mineral composition of sandstone cores before and after dissolution [70], study the order degree of rocks such as dolomite [71], and judge the differences in hydration products of cement [72]. Figure 5 shows the XRD diffractograms of a marble sample after dissolution; the chemical composition can be seen from the perspective and shape of the peaks.…”
Section: Microscopic Methodsmentioning
confidence: 99%
“…Currently, one of the primary subjects for the premature concrete structures' destruction operated in various aggressive conditions is the insufficient resistance of concrete to cyclic effects of alternate freeze-thaw [1], carbonation [2], loading [3,4], moistening, and drying [5,6], as well as to various types of corrosive effects [7]. The resistance of concrete to alternate freezing and thawing is one of the key long-term characteristics, which further determines the service life of the concrete and reinforced concrete structures made of geopolymer concrete [8], ordinary concrete [9], waste concrete [10], and pavement concrete [11,12]. Currently, the mechanism of destruction of a concrete composite during freezing and thawing, as well as the impact of various composition and technological factors on the frost resistance of concrete, are actively studied by scientists from all over the world.…”
Section: Introductionmentioning
confidence: 99%